Soluble fractions and kinetics parameters of nitrate and ammonium uptake in sunflower (“Neon” Hybrid) - Alves, Luiziene; Torres Junior, Carlos; Fernandes, Manlio; Santos, André; Souza, Sonia (Revista Ciência Agronômica, 2015)
Sunflower plants are source of oilseeds with great importance for agroenergy. Nitrogen deficiency is considered one of the factors limiting growth and yield. The objective of this study was to assess the nitrogen uptake (high and low supply of nitrate and ammonium) and to determine the uptake kinetics parameters (Km and Vmax) of these ions in sunflower plants (Neon hybrid). The experiment was carried out in a growth chamber using a hydroponic system. The following treatments were applied: 0.2 and 2.0 mmol L-1 of N-NO3- and N-NH4+. The two kinetics parameters (Km and Vmax) involved in the uptake of nitrate and ammonium were determined, as well as the soluble fractions (N-NO3-, N-NH4+, amino-N and sugars) and total N, in different plant tissues. The plants grown with ammonium showed higher Vmax than those cultivated with nitrate. High ammonium rates caused reduction of root volume and the plants supplied with 2.0 mmol L-1 of N-NO3- produced more biomass from the roots and aerial part. The highest concentrations of N-NO3- were found in the petioles. Analyzed together, the data suggest a greater potential for use of nitric-N as a nitrogen source for fertilization in the cultivation of sunflower.